Nutrient status of major Irish seaweed tides - Schrofner, Elena M. N. C. (2020)
Blooms of opportunistic, fast-growing macroalgae (commonly known as seaweed tides), are no novel occurrence, but evermore enhanced in a growing number of places by nutrient overenrichment, global warming and ocean acidification. Following their first appearance several decades ago, macroalgal blooms are shifting coastal communities and hold consequences for ecosystems and shore-based activities (e.g. shifts in primary producers, habitat loss of benthic invertebrates). The invention of nitrogen-based synthetic fertilisers in the early 20th century and increasing urbanisation, including enhanced sewage release along coasts, are considered primary causes. In this thesis dissertation, the nutrient status of the main bloom-forming macroalgal species (Ulva compressa, U. prolifera, U. rigida, Agarophyton vermiculophyllum and Pilayella littoralis) in Ireland was assessed based on tissue nutrient content. Hence, biomass abundance and nitrogen status of specimens from the four estuaries affected by the largest seaweed tides in Ireland were studied between June 2016 and August 2017 over seven sampling occasions, by collecting algal biomass and determining tissue nitrogen (N) and phosphorus (P) contents. Tissue N contents were compared to in previous studies extracted cell subsistence (Qs), and critical quotas (Qc) of the studied or similar species. The obtained results show that neither of the investigated species was limited by N at any time during the study since tissue N content exceeded Qc even during the bloom pinnacle, contrasting to the predominant conception considering N the primary limiting nutrient in cold temperate estuaries. Tissue N content was highest in winter and lowest in spring and summer, coinciding with the biomass peak (i.e. June to October), and therefore negatively correlating with biomass abundance. The results further indicate that slight increases in P might enhance bloom frequency and severity, meaning P needs to be reduced in Irish estuaries to prevent future blooms and preserve pristine coastal habitats.